2020
DOI: 10.1016/j.annemergmed.2020.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Breast Practices: Strategies to Support Lactating Emergency Physicians

Abstract: Lactation benefits both lactating individuals and their infants. Despite high rates of breastfeeding initiation, physicians are a high-risk group for early cessation. Barriers to meeting lactation goals for physicians include lack of protected time, dedicated space, and collegial support. The emergency department (ED) is a uniquely challenging setting for lactating emergency physicians, given the highstress, high-acuity environment that lacks predictability or scheduled breaks. This article presents an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Leaders in academic emergency medicine must examine their departmental policies and workplace cultures to identify factors that support or erode efforts toward achieving gender equity. 46 Departments must move beyond simply developing supportive parental leave 47 , 48 and lactation 49 , 50 policies. These are certainly necessary, yet as Cameron et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders in academic emergency medicine must examine their departmental policies and workplace cultures to identify factors that support or erode efforts toward achieving gender equity. 46 Departments must move beyond simply developing supportive parental leave 47 , 48 and lactation 49 , 50 policies. These are certainly necessary, yet as Cameron et al.…”
Section: Discussionmentioning
confidence: 99%
“…Leaders in academic emergency medicine must examine their departmental policies and workplace cultures to identify factors that support or erode efforts toward achieving gender equity. 46 Departments must move beyond simply developing supportive parental leave 47,48 and lactation 49,50 policies. These are certainly necessary, yet as Cameron et al have noted, "barriers to gender equity in academic medicine extend far beyond gaps in women's career trajectories related to (assumed, expected) maternity leave and child raising."…”
Section: Discussionmentioning
confidence: 99%
“…Education in this regard has been shown to be lacking for physicians. 26,27 In a recent article in Annals of Emergency Medicine, Haas et al 28 described strategies for supporting breastfeeding physicians in the emergency department setting. It includes strategies for lactating physicians as well as their colleagues and departmental leadership, and it bears consideration by all in PEM leadership roles.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 16 Workplace lactation barriers for physicians include clinical time pressures and lack of access to appropriate lactation spaces. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Within EM, our previous work found that cultural pressures surrounding physical separation from the department created enormous barriers to lactating while working clinically. 37 However, data elucidating the specific qualities of a lactation space that beget success remain scant.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of healthcare workers (less than 20% of whom were physicians or medical students) identified desired tangible qualities such as a hospital‐grade pump, sink, a comfortable and wipeable chair, countertop space, refrigerator, and a computer. 38 While ideal features of an ED lactation space have been recommended, 31 to date there exist no empirical, EM‐specific studies to evaluate the appropriateness of these recommendations or challenges associated with implementation. Furthermore, there exists no framework to conceptualize which modifiable qualities of a lactation space departmental leaders facing financial and space constraints should prioritize.…”
Section: Introductionmentioning
confidence: 99%